Unix for Oracle DBAs : pocket reference - Burleson, Donald Keith (O'Reilly, 2001)
The Unix for Oracle DBAs Pocket Reference puts within easy reach the commands that Oracle database administrators need most when operating in a Unix environment. If you are an Oracle DBA moving to Unix from another environment such as Windows NT or IBM Mainframe, you know that these commands are far different from those covered in most beginning Unix books. To jump start your learning process, Don Burleson has gathered together in this succinct book the Unix commands he most often uses when managing Oracle databases. You'll be able to reach into your pocket for the answer when you need to know how to: Display all Unix components related to Oracle, identify the top CPU consumers on your server, and even kill processes when necessary Stack Unix commands into powerful scripts that can perform vital DBA functions Monitor Unix filesystems, and automatically manage your trace files, dump files, and archived redo log files Use essential server monitoring commands such as top, sar, and vmstatAnd there's much more between these covers. If you need to get up to speed with Oracle on Unix, and quickly, this book is for you.